BUSINESS MODELS FOR INTEROPERABLE IOT ECOSYSTEMS - Joko Triloka (Prosiding International conference on Information Technology and Business (ICITB), 2020)
Internet of Things (IoT) was the solution on a huge number of the connected and specified “things” in the business field. Moreover, IoT companies also often transformed their applications for numerous industries. This transformation required cost strategies in designing service structures. This overview showed that the IoT ecosystem embraced the business models. The shareholders were still looking for the formula while the business ecosystems had a lack of various actors, business models, and business tools. Therefore, it was concluded that the IoT ecosystem were potential for the business models on condition that the interoperability and the interconnection of a system were well-prepared.Keywords: IoT, Interoperability, Business Model